Stability analysis of the adaptive fuzzy control system of the continuous casting process of steel of ACINOX – Las Tunas (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
Stability theory plays a central role in systems theory and engineering, is considered the most important qualitative property of linear control systems so if a system does not fulfill this condition, the rest of the specifications are meaningless. In fact, most system designs are aimed directly or indirectly to obtain stable systems to the point that it is senseless to speak of a control system if it is not stable. In dynamic systems, there are different types of stability problems and to analyze them, Lyapunov theory has a prominent place. In this paper the stability analysis of the control system is done in mold level with fuzzy adaptation process proposed for the continuous casting of steel factory Acinox Las Tunas, where will be applied first and the second Lyapunov’s methods.
Keywords: Lyapunov stability; stability analysis; fuzzy systems; adaptive control